Increasing Student Potential in the Business World through Startup Training - Mulyani, Sri; Pallu, Muhammad Saleh; Mardiana, Mardiana; Fikruddin, Muhammad; Yunus, Muhammad Kafrawi; Fatmawati, Fatmawati; Handayani, Hainun Putri; Ningsi, Sitti Warda (STKIP Singkawang, 2023)
In making a business plan, students do not have the ability and knowledge about business, innovative products, marketing, financing and choosing a good business. The purpose of this training is to equip students with enough knowledge to run a business. Implementation Methods include: problem identification, literacy studies, deepening of training materials, preparation of schedules, implementation of activities, monitoring and evaluation. Material presented: what is Star up; why should startups; Requirements to Become a Startup; Have a Vision; Advantages of a Business Startup; Good business startup; Startup Phases; Tips and Strategies; Tips for Building a Startup for College Students; Strategies for launching startups; Your Startup Publications; Tips for Managing 'Cash-flow'; What type of startup is suitable for you; Tips for Choosing a Solid Team; What about the startup's initial budget; Capital Strategy to start a Startup; Some steps to be successful for startup business people; Why businesses need Financial; Business Valuation; Types of Investors; Weaknesses of Business Startup; Why Business startups in Indonesia are rare and unpopular. The results of the starup training are 15 student business plans, namely 9 business plans in the field of fisheries by MBKM students of the Aquaculture study program, 5 business plans in the field of financial services by MBKM students of the Management study program and 1 business plan for marketing services by Agribusiness study program students. From the training activities, it can be concluded that through starup training, students get enough knowledge to run a business. Starup's knowledge must be immediately implemented and accompanied periodically to the business plan that has been made.